Estrés académico y habilidades sociales tras la pandemia por Covid 19 en estudiantes de una unidad educativa del cantón Catamayo, Periodo 2022 - Bermeo Yaguana, Lady Margaret (2022)
It is well known that covid-19 pandemic affected everyone, and even more the students who have been especially affected centrally in their educational and social environment. Therefore, the objective of this investigation was "To analyze the relationship between the levels of academic stress with the levels of social skills after COVID-19 pandemic in high school students of the "Nuestra Señora del Rosario" Fiscomisional School, period 2022". The present study was exploratory and descriptive, with a quantitative approach, cross-sectional, the results were obtained through psychometric techniques, firstly, the SISCO Inventory of Academic Stress and later the Goldstein Social Skills Scale, it was developed with a sample of 124 students of first, second and third year of high school between 15 and 17 years old; The results of the present investigation were statistically analyzed by means of the program Startical Product and Service Solutions (SPSS), obtaining as a result that there is no statistically significant correlation. Therefore, we deduce that the levels of academic stress are very noticeable in high school students and it is considered as excessive, however, it doesn´t exert a deterioration in the development of social skills, therefore, we can say that it is not a cause, however, adolescents being in an age of full changes, will experience several factors that will impede their development of social skills within their academic environment and in their daily lives